2019
DOI: 10.1038/s41416-019-0607-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of the Golgi mannosidase MAN1A1 in ovarian cancer: impact of N-glycosylation on tumour cell aggregation

Abstract: Background Maturation of complex N-glycans involves the action of Golgi mannosidases and plays a major role in cancer progression. We recently showed a favourable prognostic role of α-mannosidase MAN1A1 in breast cancer mainly caused by alteration of certain adhesion molecules. Methods We analysed the protein expression of MAN1A1 in ovarian cancer ( n = 204) using western blot and studied the impact of MAN1A1 itself and of MAN1A1-related glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Supporting our MAN1A1-centric findings, MAN1A1 has repeatedly been reported to be down-regulated in a variety of metastatic cancer cell lines including in HCC [81], CC [50], OvC [80] and PCa [82] relative to their non-metastatic counterparts. Thus, MAN1A1 and/or the resulting oligomannosidic N-glycan products may be involved (directly or indirectly) in the regulation of the growth and dissemination of some cancer types.…”
Section: Deleterious Mutations and Low Expression Of Man1a1 In Oligomannose-rich Cancerssupporting
confidence: 84%
See 1 more Smart Citation
“…Supporting our MAN1A1-centric findings, MAN1A1 has repeatedly been reported to be down-regulated in a variety of metastatic cancer cell lines including in HCC [81], CC [50], OvC [80] and PCa [82] relative to their non-metastatic counterparts. Thus, MAN1A1 and/or the resulting oligomannosidic N-glycan products may be involved (directly or indirectly) in the regulation of the growth and dissemination of some cancer types.…”
Section: Deleterious Mutations and Low Expression Of Man1a1 In Oligomannose-rich Cancerssupporting
confidence: 84%
“…Thus, this analysis indicated that reduced MAN1A1, MAN1A2, and MAN1B1 expression promotes an oligomannose-rich glycophenotype in cancer, an intuitive relationship given the known involvement of these α1,2-mannosidases in the M9-to-M5 glycan trimming process (see Figure 1). While the relative contribution of MAN1C1 (and MAN1A1/A2/B1) to the oligomannose trimming remains ill defined, recent studies have suggested that MAN1C1 plays unexpected anti-cancer roles in tumour suppression [71, 79], perhaps explaining its opposite expression pattern relative to the other α1,2-mannosidases linked to pro-tumorigenic processes (discussed below) [70, 79, 80].…”
Section: Resultsmentioning
confidence: 99%
“…The CTLA4, TOB1, MYC, Notch, Hedgehog, and EMT pathways play a critical role in cancer progression (Artym et al, 2003;Hamester et al, 2019;Jiang K. et al, 2019;Karacosta et al, 2019;Kalbasi and Ribas, 2020). Intriguingly, GSEA/GSVA results indicated that the 13 autophagy-related lncRNAs were predicted to affect all of these pathways.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, Ezrin and syntenin-1 have been shown to be linker proteins for ALCAM to anchor to the cytoskeleton [12]. Inhibition of the degree of glycosylation of ALCAM by kifunensine results in the shift of ALCAM from the membrane fraction to the cytoplasmic fraction, which also coincides with the increase in cell migration of ovarian cancer cells [13]. The change of cellular fraction of ALCAM in cancer is intriguing, and its biological and clinical impact is yet to be fully understood.…”
Section: Alcam Expression and Its Functional Influence In Cancer Cellsmentioning
confidence: 99%